Association between maternal pre-pregnancy BMI and preeclampsia: An updated systematic review and meta-analysis of cohort studies - Mussanova, Aigul; Bishekova, Balzira; Lokshin, Vyacheslav; Zhabchenko, Iryna; Dzhardemaliyeva, Nurzhamal; Nurbayeva, Tattygul; Baimussanova, Guldana (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Although several studies have previously explored the association between maternal body mass index and the risk of preeclampsia, an updated meta-analysis is necessary. This study seeks to conduct a systematic review and meta-analysis to reassess the relationship between preeclampsia and pre-pregnancy BMI, categorized into three groups—overweight, obese, and overweight & obese—and to calculate the pooled effect size (crude Odds Ratios) for each group.Methods: A comprehensive search was conducted in four electronic literature databases: PubMed, Scopus, ScienceDirect, and Google Scholar. The pooled mean effect size was calculated using a random-effects model for meta-analysis.Results: Sixteen articles were included in the meta-analysis. The pooled crude odds ratio for preeclampsia in overweight patients is 1.96 (95% CI [1.75; 2.21]), in obese patients it is 3.89 (95% CI [3.32; 4.57]), and in overweight & obese patients it is 4.19 (95% CI [3.36; 5.24]). Meta-regression did not reveal a significant association between the year of publication and the risk of preeclampsia.Conclusions: The findings confirm that higher BMI categories are associated with a significantly increased risk of preeclampsia, with the risk escalating as BMI increases. Chinese patients with lower BMI values to classify patients as overweight or obese compared to the rest of the population showed stronger associations between pre-pregnancy BMI and preeclampsia. As a result of these findings, the importance of managing weight before pregnancy is underscored, as is the importance of considering patient specific factors when assessing the risk for preeclampsia.